2021
DOI: 10.1029/2021gl093673
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Ice Microphysical Properties With Temperature and Humidity at Tops of Convective Clouds

Abstract: The sizes and shapes of ice crystals in cold clouds influence the clouds' evolution and radiative properties (Russotto et al., 2016;Jensen, Harrington, & Morrison, 2018;. In turn, the variation of ice crystal sizes and shapes within clouds are determined by a complex interaction between ice microphysics and dynamic and thermodynamic properties of the atmosphere (Bailey & Hallett, 2004). A better understanding of the many interacting processes governing the formation of complex mixtures of ice of various shapes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…These studies mainly focus on optically thick cirrus. More recently, polarized reflectance observations of the airborne Research Scanning Polarimeter (RSP) have been used to retrieve ice crystal aspect ratio and distortion levels for tops of optically thick ice clouds: van Diedenhoven et al (2012van Diedenhoven et al ( , 2020; van Diedenhoven (2021) found that crystal distortion and aspect ratio increase with cloud top height, leading to decreasing asymmetry parameters.…”
Section: Introductionmentioning
confidence: 99%
“…These studies mainly focus on optically thick cirrus. More recently, polarized reflectance observations of the airborne Research Scanning Polarimeter (RSP) have been used to retrieve ice crystal aspect ratio and distortion levels for tops of optically thick ice clouds: van Diedenhoven et al (2012van Diedenhoven et al ( , 2020; van Diedenhoven (2021) found that crystal distortion and aspect ratio increase with cloud top height, leading to decreasing asymmetry parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Diedenhoven et al found that the relative humidity has an effect on determining the temperature dependence of cloud-top ice size and shape. 20 Heymsfield et al 21 found that the macroscopic structures formed by water icing differed under different relative humidity conditions. Li et al 22 investigated the characteristics of icing on the surface of wind turbine blades by varying the relative humidity by spraying water droplets of different diameters and water mists of different flow rates, and calculated and analyzed the icing rate and icing area.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, scholars have studied humidity and ice crystal growth. Diedenhoven et al found that the relative humidity has an effect on determining the temperature dependence of cloud-top ice size and shape . Heymsfield et al found that the macroscopic structures formed by water icing differed under different relative humidity conditions.…”
Section: Introductionmentioning
confidence: 99%
“…(2017) found that by using models that have both surface roughness and air inclusions, the simulated polarized reflectance is most consistent with remote sensing observations. In recent years, remote sensing approaches have been applied to retrieve the physical properties of ice crystals quantitatively, such as surface roughness, distortion parameter, and overall morphology (Hioki et al., 2016; Saito et al., 2017; van Diedenhoven, 2018, 2021). The validity of remote sensing retrieval is nevertheless dependent on the underlying assumptions about cloud geometry and the prior light scattering models.…”
Section: Introductionmentioning
confidence: 99%